Temporal and habitat-specific variations in drivers of aboveground biomass dynamics in a Chinese subtropical forest - Yuxuan Bian; Qi Wu; Rong Zheng; Jiaqin Fu; Jianhua Chen; Xiangcheng Mi; Mingjian Yu; Yunquan Wang; Yunquan Wang; Yunquan Wang (Frontiers in Plant Science)
Understanding the mechanisms governing biodiversity-biomass relationships across temporal and spatial scales is essential for elucidating how abiotic and biotic factors influence ecosystem function in natural forests. However, the simultaneous contributions of multiple abiotic (e.g., topography) and biotic factors (e.g., structural diversity) to aboveground biomass dynamics (ΔAGB) over time and across habitat types remain inadequately understood. To address this gap, we evaluated changes in aboveground biomass across a decade and various habitats, disentangling the relative influences of topography and multidimensional diversity on ΔAGB through datasets from forest inventories conducted between 2007 and 2017, along with phylogenetic relatedness, functional traits, and environmental variables from a subtropical forest in China. Our findings indicate that aboveground biomass at community level experienced a significant decline followed by an increase over the decade, predominantly driven by changes in the low-valley habitat. In contrast, no statistically significant alterations were detected in the aboveground biomass of mid-hillside and high-ridge habitats. Furthermore, the determinants of ΔAGB exhibited temporal variation. During the 2007-2012 period, ΔAGB was primarily influenced by functional and structural diversity, accounting for 66.11% and 21.35% of relative importance, respectively. In the subsequent 2012-2017 period, phylogenetic and structural diversity emerged as key factors, explaining 48.46% and 36.43% of relative importance, respectively. Additionally, we observed that the drivers and effects impacting ΔAGB exhibited significant variability across different habitat types. In summary, our study underscores the significant spatiotemporal dependence of abiotic and biotic drivers on biomass dynamics within forest ecosystems, thereby enhancing our understanding of the complex biodiversity-ecosystem functioning relationships.